(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The capital market is a fundamental pillar of economic growth. The reality of financial markets in Arab countries reveals that most of these nations have only recently established stock exchanges. Nevertheless, they have made significant progress in developing their financial markets over the past few years. Given the global financial changes and the increasing complexity of international variables driving the globalization of financial activities and the decline of national economic boundaries, there is an urgent need to enhance Arab financial integration. This would enable these countries to keep pace with global financial developments. In this context, this study examines the feasibility of integration among Arab stock exchanges. It explores the obstacles hindering this integration, as well as the opportunities that support it, by identifying commonalities among Arab financial markets. The study also considers the potential establishment of a unified Arab stock exchange and the expected impacts of such an initiative. These impacts include facilitating capital movement among Arab countries, encouraging the repatriation of Arab investments currently held abroad, attracting more foreign investments, providing necessary funding sources for productive projects, strengthening intra-Arab trade, and paving the way for comprehensive and anticipated Arab economic integration.